Application of Sanctions for State Civil Apparatus Who Violate Personnel Discipline Case Study in Office Offices Education and Culture of Medan City - Majidah Pohan; Yasmirah Mandasari Saragih; Tamaulina Br. Sembiring (International Forum of Researchers and Lecturers, 2025)
In order to achieve national goals, a State Civil Apparatus is required, this is regulated in Article 12 of Law no. 20 of 2023 states that: